Short Communication: Characterization and nutrient analysis of seed of local cowpea (Vigna unguiculata) varieties from Southwest Maluku, Indonesia - Ritha Karuwal; SUHARSONO SUHARSONO; A. TJAHJOLEKSONO; N. HANIF (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Karuwal RL, Suharsono, Tjahjoleksono A, Hanif N. 2021. Short Communication: Characterization and nutrient analysis of seed of local cowpea (Vigna unguiculata) varieties from Southwest Maluku, Indonesia. Biodiversitas 21: 85-91. Cowpea (Vigna unguiculata (L.) Walp.) is a legume species that have many local varieties across regions in Indonesia, including in Southwest Maluku District. It has been utilized by the community as raw materials, but mainly for food sources of self-consumption. While there are rich local varieties of cowpea in Southwest Maluku, the data about its morphological characters and nutritional compositions are not available. The objectives of the research were to analyze morphological characters and nutritional compositions of local seven cowpea varieties from Southwest Maluku and classify these varieties according to such characters and compositions. Morphological characters observed consisted of shape, color, texture, eye pattern, eye color, size (length, width, thickness), and 100-grain weight. Nutritional composition consisted of proximate analysis tested using AOAC (Association of Official Analytical Chemist) method and folic acid content using HPLC (High-Performance Liquid Chromatography) method. The results showed that the varieties have significant variation in morphological characters and nutrition composition. There are differences in shape, color, texture, eye pattern, and color. Seed size in terms of length, width and thickness have range values of 5-9 mm, 4-6 mm, 3-4 mm, respectively while seed weight ranges 11-19 g. Furthermore, nutrition composition is significantly affected by varieties. Moisture content ranges between 11-17%, ash content of 3.13-3.97%, fat content of 0.58-1.42%, protein of 15.5-20.76%, carbohydrate of 58.46-63.48% and folic acid content of 100.13-131.57 µg/mL. There is significant correlation between morphology characters and nutrition composition. Principal Component Analysis (PCA) showed that local varieties can be classified into three clusters. Therefore, KM1, KM3, KM4 and KM7 varieties that have the highest size, weight, and nutrition composition can be selected in plant breeding.